2012
DOI: 10.1111/j.1526-4610.2012.02152.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene‐Related Peptide and Size of the Atrial Septal Defect in New‐Onset Migraine After Transcatheter Closure: Results of a Preliminary Study

Abstract: Bigger ASD size and lower plasma CGRP levels before closure can be a potential predictor of new-onset MHAs. Furthermore, a significant increase of CGRP levels during migraine attack implies that the occurrences of new-onset MHAs after ASD closure correlate with the release of CGRP. This suggests CGRP sensitization from a lower baseline may be involved in the occurrence of new-onset MHAs after ASD closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 32 publications
(74 reference statements)
1
21
1
Order By: Relevance
“…De novo MH following pASDC was reported in two of three prospective studies (71, 72). Luermans et al (71) reported de novo MH in 4/63 patients (6%) after the procedure.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…De novo MH following pASDC was reported in two of three prospective studies (71, 72). Luermans et al (71) reported de novo MH in 4/63 patients (6%) after the procedure.…”
Section: Resultsmentioning
confidence: 94%
“…In terms of study type, change in preexisting MH was reported in 3 of 8 case studies (62, 70, 82); 2 of 3 prospective studies (71, 84), and in 9 of 13 retrospective studies (19, 52, 5961, 63, 64, 76, 81). De novo MH was reported in 5 of 8 case studies (57, 73, 75, 78, 92), in 2 of 3 prospective studies (71, 72), and in 11 of 13 retrospective studies (19, 46, 51, 52, 58, 61, 64, 67, 77, 81, 93). Finally, a recent randomized controlled trial reported de novo MH following pASDC (79).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations